First measurement of heavy flavour femtoscopy in Au+Au collisions at √sNN = 200 GeV by STAR - Roy Chowdhury Priyanka (EPJ Web of Conferences)
In the very beginning stages of heavy-ion collisions, hard partonic scatterings yield heavy quarks, which go through the entire Quark-Gluon Plasma medium evolution. Femtoscopic correlation is characterized as a two particle correlation at low relative momentum that depends on the size of the region from which the correlated particles are emitted and on the final-state interaction. Such correlations between identifiable charged hadrons and charmed mesons could provide insights into their interactions with the medium and charm quarks in the hadronic phase. We describe the first femtoscopic correlation measurements made by the STAR experiment between D0/D¯0 - π± pairs at mid-rapidity in Au+Au collisions at √sNN The discussion of the physics consequences involves a comparison to theory calculations.